2021
DOI: 10.1002/pssr.202000589
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Field‐Induced Ferroelectricity in 5%Y‐doped Hf0.5Zr0.5O2: Transformation from the Paraelectric Tetragonal Phase to the Ferroelectric Orthorhombic Phase

Abstract: The ferroelectric phase transformation from the tetragonal phase to the orthorhombic phase, induced by an electric field, is demonstrated in a 5%YO1.5‐doped Hf0.5Zr0.5O2 epitaxial film which is grown on Sn‐doped In2O3‐covered (111) yttria‐stabilized zirconia by the pulsed laser deposition method at room temperature and subsequent heat treatment. Although X‐ray diffraction shows the film to consist of a paraelectric tetragonal phase after the heat treatment, polarization–electric field (P–E) measurements reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Less (100) and (110) signal is observed for the 10:1 sample. While this might be explainable by increased tetragonal phase, this would not match to the electrical results, as other groups have reported that super-cooled tetragonal phase does not result in AFE-like behavior but reduced P R and P S [20,21]. Moreover, the shape of the {200} -peak is slightly changed for the 10:1 sample, as indicated by the smaller TiN-related shoulder and reduced intensity of the (200) shoulder at smaller angles.…”
Section: Invited Papermentioning
confidence: 64%
See 3 more Smart Citations
“…Less (100) and (110) signal is observed for the 10:1 sample. While this might be explainable by increased tetragonal phase, this would not match to the electrical results, as other groups have reported that super-cooled tetragonal phase does not result in AFE-like behavior but reduced P R and P S [20,21]. Moreover, the shape of the {200} -peak is slightly changed for the 10:1 sample, as indicated by the smaller TiN-related shoulder and reduced intensity of the (200) shoulder at smaller angles.…”
Section: Invited Papermentioning
confidence: 64%
“…unlikely as an origin for AFE-like behavior, since the operating temperature is far below the Curie temperature [31,32] and recent investigations demonstrated the irreversible nature of this phase transition [20,21]. Internal bias fields and domain wall pinning on the other side would require diffusion/drift processes during wake-up, which are not observed [22].…”
Section: Invited Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Its origin is discussed in more detail below. The second is electric field-induced t–o transition, which is usually considered the cause of the high polarization that some polycrystalline ZrO 2 and Zr-rich Hf 1– x Zr x O 2 films can present. ,,, It has to be noted that field-induced t–o transition in polycrystalline films requires a large number of cycles, ranging from 160 to thousands. , Field-induced t–o transition has been also reported very recently in epitaxial Y-doped HZO, presenting the films’ wake-up effect too, up to about 100 cycles . In contrast, there is no wake-up effect in our epitaxial ZrO 2 films (Supporting Information, Figure S6).…”
Section: Resultsmentioning
confidence: 98%